Usage of Land Use/Land Cover and Anthropogenic Parameters in Prioritizing Conservation in Sub Watersheds of Upper Pulangi River - Shiella Lynn Goyo; George Puno (East Asian Journal of Multidisciplinary Research, 2023)
Most part of the Philippines are located within watersheds. The best unit for managing natural resources like land and water is a watershed. This study aimed to prioritize the nine sub watersheds of Upper Pulangi River for conservation and rehabilitation using land use and land cover and anthropogenic parameters. Land cover and land use was analysed using remote sensing and GIS techniques to identify and delineate its categories. In terms of anthropogenic parameters, watersheds with the most extensive and highest human alterations, such as surface mining/quarries, illegal logging, land conversion to agriculture, kaingin, built-up areas, and upland settlers, were assigned the top priority for conservation. Watershed prioritization is the process of ranking different sub-watersheds in the order in which they must be addressed for soil conservation measures. Out of the nine sub watersheds being studied, the results showed that Sawaga sub watershed has the high priority for conservation followed by Maapag, Upper Pulangi, Taganibong, and Malingun sub watersheds with medium priority. Panlibatuhan, Tigwa and Taganibong sub watersheds fall under low priority while Manupali sub watersheds has the lowest priority due to its favourable vegetation cover and existing conservation and rehabilitation projects. It is recommended to watershed managers of Upper Pulangi river to prioritize and consider for funding the rehabilitation and soil conservation measures for Sawaga sub watershed. The methods used in this study can be applied to other watershed management under limited resources.